Genotypes of rubella virus and the epidemiology of rubella infections in the Democratic Republic of the Congo, 2004–2013. Issue 10 (5th April 2016) - Pukuta, Elizabeth; Waku‐Kouomou, Diane; Abernathy, Emily; Illunga, Benoit Kebela; Obama, Ricardo; Mondonge, Vital; Dahl, Benjamin A.; Maresha, Balcha G.; Icenogle, Joseph; Muyembe, Jean‐Jacques
Abstract : Rubella is a viral infection that may cause fetal death or congenital defects, known as congenital rubella syndrome (CRS), during early pregnancy. The World Health Organization (WHO) recommends that countries assess the burden of rubella and CRS, including the determination of genotypes of circulating viruses. The goal of this study was to identify the genotypes of rubella viruses in the Democratic Republic of the Congo (DRC). Serum or throat swab samples were collected through the measles surveillance system. Sera that tested negative for measles IgM antibody were tested for rubella IgM antibody. Serum collected within 4 days of rash onset and throat swabs were screened by real‐time RT‐PCR for rubella virus RNA. For positive samples, an amplicon of the E1 glycoprotein gene was amplified by RT‐PCR and sequenced. 11733 sera were tested for rubella IgM and 2816 (24%) were positive; 145 (5%) were tested for the presence of rubella RNA by real‐time RT‐PCR and 10 (7%) were positive. Seventeen throat swabs were analyzed by RT‐PCR and three were positive. Sequences were obtained from eight of the positive samples. Phylogenetic analysis showed that the DRC rubella viruses belonged to genotypes 1B, 1E, 1G, and 2B. This report provides the first information on the genotypes of rubella virus circulating in the DRC. These data contribute to a better understanding of rubella burden and the dynamics of rubella virus circulation in Africa. Efforts to establish rubella surveillance in the DRC are needed to support rubella elimination in Africa. J. Med. Virol. 88:1677–1684, 2016 . © 2016 Wiley Periodicals, Inc.